2015
DOI: 10.1002/cncr.29372
|View full text |Cite
|
Sign up to set email alerts
|

Frontline rituximab monotherapy induction versus a watch and wait approach for asymptomatic advanced‐stage follicular lymphoma: A cost‐effectiveness analysis

Abstract: BACKGROUND: A watch and wait (WW) strategy is the standard of care for patients with asymptomatic advanced-stage follicular lymphoma. Recent data have demonstrated an improvement in the time to progression with rituximab induction (RI) with or without rituximab maintenance (RM) in comparison with a WW strategy wait in such patients. It remains unclear whether this is a costeffective strategy. METHODS: A Markov decision analysis model was developed to compare the clinical outcomes, costs, and costeffectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…One of the distinguishing features of this analysis in comparison to previous economic evaluations of watchful waiting and active treatment in other disease areas, was that there was assumed to be no QoL benefit for patients on watchful waiting in comparison to active treatment. This is consistent with the data from the randomised study which showed that QoL with rituximab was at least as good as, and probably better than, watchful waiting (Prica et al, 2015).…”
Section: Resultssupporting
confidence: 90%
“…One of the distinguishing features of this analysis in comparison to previous economic evaluations of watchful waiting and active treatment in other disease areas, was that there was assumed to be no QoL benefit for patients on watchful waiting in comparison to active treatment. This is consistent with the data from the randomised study which showed that QoL with rituximab was at least as good as, and probably better than, watchful waiting (Prica et al, 2015).…”
Section: Resultssupporting
confidence: 90%
“…The cost effectiveness of first-line treatments was evaluated in eight studies (seven for FL, one for FL and MZL) [7][8][9][10][11][12][13], and nine studies reported cost-effectiveness of maintenance treatment [14][15][16][17][18][19][20][21]. Six studies were found to report cost effectiveness of treatments for relapsed/refractory (R/R) FL, while only three studies reported cost-effectiveness evidence for refractory FL.…”
Section: Model/analysis Design Overviewmentioning
confidence: 99%
“…R-MCP versus MCP was projected to have an ICER ranging between £4861/QALY gained [9] and £9316/QALY gained (GBP; 2010) [9]. [10], and R monotherapy was dominant over watchand-wait for FL [10]. Additionally, B + R versus R-CHOP was projected to have an ICER of $27,398/QALY gained (CAD; 2012) for FL and $10,012/QALY gained (CAD; 2012) for MZL [10].…”
Section: First-line Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, results from these randomized trials suggest that an aggressive maintenance rituximab strategy does not significantly impact OS compared with initial observation or first-line rituximab treatment without maintenance, at least within the reported timeframe of follow-up. From a pharmacoeconomics point of view, the implications of these trials on resource use are likely to be substantial [18].…”
Section: Rituximab In the First-line Treatment Of Indolent Non-hodgkimentioning
confidence: 99%